Exploring PTPN6 as a dual oncogenic and immunological marker in melanoma - Piaopiao Bian; Shaoyan Liu; Qiuping Luo; Zewen Feng; Sanyan Li; Wei Zhang (Discover Oncology)
Abstract Melanoma is an aggressive form of skin cancer known for its ability to avoid detection by the immune system and resist treatment. This study explores the role of PTPN6, a protein linked to lactate, as both an oncogene and an immune-related biomarker in melanoma. Using computational tools, we examined the expression and mutation patterns of lactate-related genes in skin cutaneous melanoma (SKCM) and identified different patient groups based on prognosis. Our results show that PTPN6 plays a key role in regulating immune responses, affecting the behavior of immune cells. This suggests that PTPN6 could be a promising target for new therapies. By combining insights from metabolism and immunology, our research lays the groundwork for personalized treatments that may improve outcomes for melanoma patients.